Design of Distributed Drive Control Strategy for Wheel Side Rear Drive Electric Bus Based on Neural Network Algorithm - Chen, Huipeng; Zheng, Yingjie; Chen, Sen; Zhu, Shaopeng; Gao, Jian (Frontiers in Bioengineering and Biotechnology, 2022)
The electric bus driven by the wheel-side motor has a natural advantage for the driving stability control of the vehicle because the torque of each driving wheel is independently controllable. Based on the advantages of the artificial neural network control algorithm, this paper designs a direct yaw torque control strategy based on neural network PID control, and combines the steering characteristics of the vehicle to distribute the driving torque. The co-simulation results of Matlab/Simulink and TruckSim show that the designed control strategy can effectively reduce the vehicle’s center of mass slip angle and lateral acceleration under medium and high speed conditions, and ensure the stable driving of the bus.